THE METHOD FOR PREDICTING THE TYPE OF SCAR TISSUE IN THE TREATMENT OF BURN WOUNDS - Yu. V. Yurova; E. V. Zinoviev; K. M. Krylov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. We wanted to relate the perfusion index (M) in burn wound in the period of treatment with the development of the type of pathological scar tissues of different origin during the convalescence period. METHODS AND MATERIALS. We studied burn wounds and scars in 25 patients with thermal trauma in the postoperative period and the convalescence period during the year. We determined the values of perfusion of burn wounds with help of laser Doppler flowmetry, which were diagnostically significant for predicting the outcome of treatment of burn wounds. RESULTS. If the perfusion index was lower than 4.0 PU and higher than 10 PU, then a high risk of developing the pathological type of scar tissue was predicted. If the perfusion index was between 4.0 and 10 PU, then a minimal risk of developing the pathological type of scar tissue was predicted. CONCLUSION. The perfusion index is an important criterion for choosing early preventive measurements and specialized treatment of burn wounds to reduce probable developing the pathological scars and, as a result, obtaining good cosmetic and functional effects. Based on the results of the study, we developed the diagnostic algorithm for predicting the development of various types of scar tissue. Keywords: deep burns, predicting the type of scars, scars, microcirculation, laser Doppler flowmetry, burn wound, outcome of treatment of burn wounds